Tuning the Kondo resonance in two-dimensional lattices of cerium molecular complexes. Issue 19 (3rd May 2018) - Granet, Julien; Sicot, Muriel; Kierren, Bertrand; Lamare, Simon; Chérioux, Frédéric; Baudelet, François; Fagot-Revurat, Yannick; Moreau, Luc; Malterre, Daniel
Abstract : The Kondo effect in Ce-based double-decker molecular self-assembly can be observed or not depending on the substrate. Abstract : Cerium intermetallics have raised a lot of interest for the past forty years thanks to their very unusual and interesting electronic and magnetic properties. This can be explained by the peculiar electronic configuration of Ce (4f 1 ) that allows different oxidation states leading to singular behavior such as quantum phase transitions, heavy-fermion behavior and the Kondo effect. In this work, we used a mixed-valence molecular analogue to study the Kondo effect down to the atomic scale by means of scanning tunneling microscopy/spectroscopy (STM/STS) for which new many-body effects are expected to emerge due to reduced dimensionality and specific chemical environment of the 4f-ion. For that purpose, double-decker molecular complexes hosting a Ce ion were synthesized and adsorbed onto Ag and Cu (111) surfaces forming two-dimensional lattices. As a result, we observed a zero-bias conductance resonance on Ag only indicative of a Kondo effect arising from the coupling between a molecular spin and the conducting electrons of the metallic surface. The emergence of the Kondo effect is discussed in terms of intermolecular and molecule/substrate interactions. This work expands the little knowledge to date on the structural and related electronic properties of Ce-based molecular systems on surfaces. In particular, it shows that Ce-based double deckers are good platforms to obtain insight into 4f-induced many-body effects down to the nanometer scale and in two-dimensional lattices. Moreover, this outcome has a strong impact for future applications of molecular devices in which both metals are commonly used as electrical contacts.